2018
DOI: 10.1093/humrep/dey119
|View full text |Cite
|
Sign up to set email alerts
|

Increased AIF-1-mediated TNF-α expression during implantation phase in IVF cycles with GnRH antagonist protocol

Abstract: This work was supported by grants from the National Natural Science Foundation of China, Grant numbers 81771656 and 81370763; Clinical research special fund of Chinese Medical Association, Grant number 16020480664; Shanghai Jiao Tong University Medicine-Engineering Fund, Grant number YG2017ZD11 and YG2017MS57; and the Merck-Serono China Research Fund for Fertility Agreement. P.C.K.L. is supported by a Canadian Institutes of Health Research Foundation Scheme Grant 143317. None of the authors has any competing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
0
26
1
Order By: Relevance
“…Accordingly, the number of pregnancies in the Fluoxetine group was twice as many as that in the control group and also an increase in TNF-α did not affect the pregnancy rate. Unlike our results, the findings of the studies done by Xu et al (2018) and Boudjenah et al (2014) showed that an increase in the TNF-α serum levels caused disorders in the embryo implantation, as a result of which there was a decrease in pregnancy rate during IVF 36,37 . According to Lee et al, an increase in the TNF-α level decreases the quality, but not the number of oocytes and there is no relationship between its level and pregnancy 8 .…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, the number of pregnancies in the Fluoxetine group was twice as many as that in the control group and also an increase in TNF-α did not affect the pregnancy rate. Unlike our results, the findings of the studies done by Xu et al (2018) and Boudjenah et al (2014) showed that an increase in the TNF-α serum levels caused disorders in the embryo implantation, as a result of which there was a decrease in pregnancy rate during IVF 36,37 . According to Lee et al, an increase in the TNF-α level decreases the quality, but not the number of oocytes and there is no relationship between its level and pregnancy 8 .…”
Section: Discussioncontrasting
confidence: 99%
“…RL95-2 cells were cultured in 35-mm plates (3 × 10 5 cells) and grown with the transfected GLUT1 siRNA or NC treatments. JAR cells were pretreated with diluted (0.5 mM) CellTrace ™ CFSE (Invitrogen, Carlsbad, CA, United States) medium for 30 min, and the cells suspension was added to plates containing RL95-2 cell monolayer, which were gently shaken (40 rpm) 1 h at 37°C (Choi et al, 2017;Xu et al, 2018). Then, the cell culture supernatant was removed, the plates were washed with PBS, the images were acquired using a fluorescent microscope, and the number of attached cells were counted using Image-Pro Plus software (Media Cybernetics Inc., Silver Spring, MD, United States).…”
Section: In Vitro Adhesion and Invasion Assaymentioning
confidence: 99%
“…Tubal factor infertility cases caused by hydrosalpinx, salpingitis, etc., were excluded. The inclusion and exclusion criteria for both groups were the same as described previously (Guo et al, 2018;Xu et al, 2018). In addition, for the isolation of primary EECs and ESCs, another Data presented as mean ± SD or frequency.…”
Section: Participants and Endometrial Biopsiesmentioning
confidence: 99%
“…The human EEC line Ishikawa was obtained from European Collection of Authenticated Cell Cultures (ECACC), and were authenticated by DNA profiling using short tandem repeat (STR) analysis (Supplementary Figure S1A) and mycoplasma free (Supplementary Figure S1B). Isolation of primary human EECs and ESCs was performed as previously described (Xu et al, 2018) . Briefly, endometrial biopsy samples were processed within 4 h of collection.…”
Section: Cell Culturementioning
confidence: 99%